Design, Synthesis, and Molecular Docking Studies of Curcumin Hybrid Conjugates as Potential Therapeutics for Breast Cancer - Siva S. Panda; Queen L. Tran; Pragya Rajpurohit; Girinath G. Pillai; Sean J. Thomas; Allison E. Bridges; Jason E. Capito; Muthusamy Thangaraju; Bal L. Lokeshwar (MDPI AG, 2022)
Curcumin (CUR) has received great attention over the past two decades due to its anticancer, anti-inflammatory, and antioxidant properties. Similarly, Dichloroacetate (DCA), an pyruvate dehydrogenase kinase 1 (PKD1) inhibitor, has gained huge attention as a potential anticancer drug. However, the clinical utility of these two agents is very limited because of the poor bioavailability and unsolicited side effects, respectively. We have synthesized fusion conjugates of CUR and DCA with an amino acids linker to overcome these limitations by utilizing the molecular hybridization approach. The molecular docking studies showed the potential targets of Curcumin-Modified Conjugates (CMCs) in breast cancer cells. We synthesized six hybrid conjugates named CMC1-6. These six CMC conjugates do not show any significant toxicity in a human normal immortalized mammary epithelial cell line (MCF10A) in vitro and C57BL/6 mice in vivo. However, treatment with CMC1 and CMC2 significantly reduced the growth and clonogenic survival by colony-formation assays in several human breast cancer cells (BC). Treatment by oral gavage of a transgenic mouse BC and metastatic BC tumor-bearing mice with CMC2 significantly reduced tumor growth and metastasis. Overall, our study provides strong evidence that CUR and DCA conjugates have a significant anticancer properties at a sub-micromolar concentration and overcome the clinical limitation of using CUR and DCA as potential anticancer drugs.